Covid-19 infected lung detection using machine learning - Islam, Md. Muntaha; Afiat, Mashfurah; Biswas, Adrita; Syffullah, Md Khalid; Rishan, Asadur Rahman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.